DIPEPTIDYL PEPTIDASE-4 INHIBITORS: SENSITIVITY MARKERS - Iskakova , A.N.; Aitkulova , A.M.; Sikhayeva , N.S.; Romanova , A.A.; Maratkyzy , L.; Akanov , Zh.A.; Zholdybayeva , E.V. (Eurasian Journal of Applied Biotechnology, 2017)
Type 2 diabetes is a common disease worldwide. Control of blood glucose level is important for effective therapy in patients with type 2 diabetes. Inhibitors of dipeptidyl peptidase-4(DPP-4) regulate blood glucose levels by increasing incretin hormone activity by blocking the enzyme DPP-4. Many drugs have negative side effects resulting inadverse drug reactions, which can ultimately lead to ineffective therapy. Drugs do not always work the same way for everyone, yet many currently available drugs are designed as “one size fits all” solution. Predicting who will benefit from a medication and who will not respond at all, or who will experience negative side effects is difficult. Pharmacogenomics is the study of how a person’s genes affect their response to drugs. Here, we identify and examine molecular genetic markers affecting the efficiency of DPP-4 inhibitor therapy. We identified CYP1A2 rs762551 and UGT2B7 rs7668258 to be associated with type 2 diabetes risk. Furthermore, we showed that CYP1A2 rs762551 and UGT2B7 rs7668258 can be usedas prognostic markers for complications, and as sensitivity markers for DPP-4 inhibitor therapy. Moreover, ABCB1 rs1128503 and NAT2 rs1041983 were identified as molecular markers of DPP-4 treatment effectiveness and NAT2rs1041983 is responsible for the cardioprotective effects of DPP-4 inhibitors, irrespective of therapy effectiveness.